The state of bone mineral density in the prolapse of the pelvic organs - Il'nur I. Musin; Timur B. Minasov; Raisa A. Naftulovich; Elena M. Popova; Karina N. Mingareeva; Edvard A. Berg; Anzhella R. Molokanova; Polina A. Berg (IP Berlin A.V., 2021)
Background. Plausible predictions of future mortality and disability are useful aids in making decisions about priorities for medical research. Recent advances in medicine have led to the fact that some countries, such as Japan, have the highest life expectancy in the world. Osteoporotic fractures make a significant contribution to the development of morbidity and mortality in the aging population. Despite an active study of the mechanisms of the development of pelvic organ prolapse and disorders of bone mineral density separately, the general background of these diseases has previously been little studied. Aim. To study bone density according to densitometry data in peri- and postmenopausal women. Materials and methods. To carry out this study, 2 groups of women were formed. The first (experimental) group included 76 women admitted for routine surgical treatment of genital prolapse, the second group (control) 68 women without clinical manifestations of pelvic floor descent, who underwent a medical examination by a gynecologist on an outpatient basis. Results. Analysis of extragenital diseases in women included in the study showed a high prevalence in the experimental group of hypertension (p=0.028), osteochondrosis (p=0.001), scoliosis (p=0.028), hemorrhoids (p=0.013). Also, women in this group more often noted stretch marks on the skin (p=0.002) and were more often operated on for other diseases (p=0.043), which indicates the association of genital prolapse with undifferentiated connective tissue dysplasia and hypertension. The diagnosed severe osteoporosis (according to 1 or more densitometry indicators, where the T-score is less than -2.5) had a direct correlation with the duration of menopause. For a detailed analysis of the factors influencing severe osteoporosis in peri- and postmenopausal women, logistic regression analysis and ROC analysis were performed. The independent variable was the presence of severe osteoporosis, and the dependent variables were: stage according to POP-Q, the presence of hypertension, the presence of diabetes mellitus in history. Conclusion. This study confirms the presence of a comorbidity decrease in bone density according to densitometry and the presence of hypertension (p=0.028) and genital prolapse. According to the ROC analysis, an increase in the stage of genital prolapse according to the POP-Q classification increases the risk of developing severe osteoporosis.